Psychological Problem in Children with a Disorder of Sex Development and Their Relatives: A Narrative Literature Review - Erlangga Danu Saputro (Open Access Indonesian Journal of Medical Reviews, 2021)
Disorder of sexual development (DSD) is a challenging disorder that must be done clinically and physiologically. The patients and relatives may experience various psychosocial problems that impact their lives. This study aimed to describe psychological problems in children with DSD and their relatives. Psychosocial and social-environmental problems and management of DSD that are identified in earlier times can reemerge during childhood. Diagnosing a child with a rare disorder, such as mosaic sex chromosome DSD, is often stressful for parents and families. Parents' stress levels and coping strategies are influenced by the diagnosis, type of disease, severity, cause, and presence of non-invasive, invasive, surgical, mental, and behavioral changes and treatment or therapy. In conclusion, psychosocial care for patients and relatives affected by a disorder of sex development is currently limited. Families struggle with challenges such as genetic information, medical complexity, anatomical differences (whether or not surgery is done), surgical complications, lack of clarity in some gonadal tumor risks, doubt about the stability of the child's gender identity, and fertility potential.